Hydrogen release from liquid organic hydrogen carrier using plate catalysts in continuous and dynamic operation - Nathrath, Phillip; Baier, Benjamin; Herz, N; Wituschek, Simon; Raed Ramzi, Yousuf; Merklein, Marion; Li, M.; Lederle, F.; Wasserscheid, Peter; Hübner, E.G.; Schühle, Patrick (Chemical Engineering Journal, 2025)
Significant fluctuations in energy supply are anticipated with the increasing utilization of renewable energy sources. To mitigate these fluctuations, green hydrogen released from Liquid Organic Hydrogen Carrier (LOHC) systems offers a promising solution. The use of plate catalysts in novel continuous reactor configurations enables favorable heat and mass transfer rates to drive this highly endothermic hydrogen release reaction. These catalytic plate reactors facilitate dynamic operation modes for an effective response to rapid changes in hydrogen and energy demand. In this study the performance of an established spray-coated plate catalyst is tested for the first time in continuous and dynamic operation modes. In detail, the productivity in hydrogen release from the LOHC-molecule perhydro benzyltoluene (H12-BT) is determined using a catalytic plate reactor and a tailored restart protocol was developed to maintain high hydrogen release productivities after a reactor shutdown. The plate catalysts showed good activity of up-to 0.25 mgH2 min−1 cm−2, a highly dynamic response in hydrogen release and an excellent stability under stationary and fluctuating conditions. Furthermore, a novel non-additive manufacturing method for plate catalysts through laser-texturing is introduced. The morphology of these new structures is characterized and their dehydrogenation performance is compared to the superior spray-coated benchmark.
CRIS-Team Scopus Importer:2025-02-07
Keywords: Benzyltoluene; Dehydrogenation; Laser-texturing; LOHC; Plate reactor